Зооморфные мотивы в декоре древнерусских изделий из кости с территории Лесостепного Поднепровья - Сергеева, М. С. (Давнина. Харківський історико-археологічний щорічник, 2016)
SUMMARY Sergeyeva M.S. Zoomorphic Motives in the Decorum of Ancient Russian Handicrafts of Bone From the Territory of Pridnieper Forest-Steppe The article gives semantic analysis of zoomorphic Images on ancient Russian bone handicrafts. It was found out that the volumetric, relief and contour fretwork was applied for the usage of zoomorphic decorum. The emergence of these items in Russia is connected with the general European renaissance of the «animal style ». Admitting mythological sources of zoomorphic patterns, the author proves that in X — XIII centuries most of them did not have a mythological content, but a symbolic one.